Carcass characteristics of lambs fed diets with mulberry hay - Cirne, Luís Gabriel Alves; Da Silva Sobrinho, Américo Garcia [UNESP]; De Almeida, Fabiana Alves [UNESP]; Santana, Valéria Teixeira [UNESP]; Endo, Viviane [UNESP]; Zeola, Nivea Maria Brancacci Lopes [UNESP]; De Almeida, Amelia Katiane [UNESP] (Universidade Estadual de Londrina, 2016)
The aim of this study was to evaluate the in vivo quantitative traits of carcass and commercial cuts of lambs fed diets containing 0, 12.5, and 25.0% mulberry hay replacing the concentrate. Twenty-four Ile de France lambs at approximately 60 days of age, with 15 kg body weight, were confined in individual stalls and slaughtered at 32 kg. Increasing levels of mulberry hay in the diet resulted in a linear increase in chest depth (R2=0.84), leg muscularity index (R2=0.71), and muscle:bone ratio (R2=0.95); a linear decrease in leg compactness index (R2 =0.75), shoulder weight (R2=0.78), and femur weight (R2=0.99) and length (R2=0.86); and a quadratic response from chilling losses (R2=1.0) and percentage of intermuscular fat. Mulberry hay can be used in the feeding of feedlot lambs without compromising their carcass quantitative characteristics.
Keywords: Cuts; Morphology; Nutrition; Sheep; Yield